The Prevalence of Fentanyl in Drug-Related Deaths in Philadelphia 2004–2006 - Stella C. Wong; Lisa Mundy; Rebecca Drake; John A. Curtis; William E. Wingert (Journal of Medical Toxicology, 2010)

Riverine export and the effects of circulation on dissolved organic carbon in the Hudson Bay system, Canada - C. J. Mundy a; Michel Gosselin; Michel Starr; Christine Michelc (Limnology and Oceanography, 2010)
The distribution of dissolved organic carbon (DOC) in Hudson Bay (HB), Foxe Basin (FB), and Hudson Strait (HS) was examined during 01‐14 August 2003. The HB system displayed relatively high DOC concentrations with medians of 109, 90, and 100 mmol L −1 for measurements made in HB, FB, and HS, respectively. Waters were significantly modified as they circulated through the HB system. An influence of marine‐derived DOC was inferred for waters entering the system from northern HS and FB. The presence of a cold‐water layer and elevated DOC concentrations observed in HB along the western coast and at depth was explained through either brine rejection and export of surface DOC to depth during sea ice formation or the decomposition of a settling algal bloom. As waters circulated in HB, an input of terrigenous DOC was the dominant modifying factor. In particular, DOC‐laden rivers in southern HB increased the DOC concentration and then displayed a conservative behavior as water exited the bay along the southern coast of HS. Additionally, the late stages of ice melt observed during this study showed a significant dilution effect on surface DOC concentrations within eastern HB. Input and export of riverine DOC in the HB system was estimated at ~5.5 Tg C yr −1 , which is approximately 23% of the annual DOC input from rivers draining directly into the central Arctic Ocean and therefore represents an important contribution of terrigenous carbon to northern seas.